Ketaatan Muslim Indonesia terhadap Penetapan Hari Raya antara Itsbat Pemerintah dan Ikhbar Ormas Islam - Rohmah, Nihayatur (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2019)
The issue of “hisab rukyat” in terms of determining the beginning of the Islamic month often makes a difference. Government efforts through itsbat trial basically are based on efforts to achieve uniformity, benefit and unity of Indonesian Muslims. But in the level of reality, it turns out that each party (read; religio social organizations) issued its own decision. Religion has an influence as a motivation in encouraging individuals to carry out an activity, because actions carried out against the background of religious beliefs are considered to have an element of purity and obedience. This connection will influence someone to do something. Then came the Islamic groups who wanted to compromise with the government and Islamic groups who continued to fight outside the system with the wider community. Regulations are less effective if the degree of compliance only revolves around compliance (obeying for fear of being sanctioned) or identification (obeying only because of fear of good relations with someone being damaged). Conversely, if the degree of compliance reaches internalization (obedience to a rule because he truly feels that the rule is material and his spirit is in accordance with the intrinsic values ??adopted), it means the quality of the effectiveness of the regulation is very high, so the system runs according to the rules existing without stressing the strict control function. Of the three motives of obedience it is very likely to be the basis for consideration of the Muslim community in Indonesia to prefer to compromise with the government or mass organizations in terms of the determination of the holiday.